(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article describes the results of research on drying different varieties of apples. Experiments were carried out to study the criteria of indicators important for evaluating the organoleptic properties of apple fruit after drying. As a result of the research, scientifically based conclusions are made.